+0  
 
+5
249
4
avatar+21 

This is Similar to my first question (The one Melody helped me solve),

 

$$\\2x^2+8x-12=0\\\\2(x^2+4x-6)\\\\x^2-2x+6x-6\\$$

 

So I did this^ and then I changed the bottom problem to this. V

 

$$\\x(x-2)+6(x-1)\\\\(x+6)(2x-3)\\$$

 

I am wondering if this is correct, if not where did I make a mistake?

 

~Purpe

Purpe  Aug 16, 2015

Best Answer 

 #1
avatar+26329 
+10

$$\\
2x^2+8x-12=0\\\\
\text{Since each coefficient is a multiple of 2, divide each term by 2}\\\\
x^2+4x-6=0\\\\
\text{This does not factorise nicely so add and subtract 4:}\\\\
x^2+4x+4-4-6=0\\\\
(x+2)^2-10=0\\\\
(x+2)^2=10\\\\
x+2=\pm\sqrt{10}\\\\
x=-2\pm\sqrt{10}$$

Alan  Aug 16, 2015
Sort: 

4+0 Answers

 #1
avatar+26329 
+10
Best Answer

$$\\
2x^2+8x-12=0\\\\
\text{Since each coefficient is a multiple of 2, divide each term by 2}\\\\
x^2+4x-6=0\\\\
\text{This does not factorise nicely so add and subtract 4:}\\\\
x^2+4x+4-4-6=0\\\\
(x+2)^2-10=0\\\\
(x+2)^2=10\\\\
x+2=\pm\sqrt{10}\\\\
x=-2\pm\sqrt{10}$$

Alan  Aug 16, 2015
 #2
avatar+26329 
+5

Purpe wrote "I am wondering if this is correct, if not where did I make a mistake?"

 

Your last line doesn't follow from your next-to-last-line.  All lines but your last are correct; however, they don't lead towards a solution, so are not useful here.

Alan  Aug 17, 2015
 #3
avatar+91051 
+5

Hi Purpe,

Alan is right. Only expressions with rational roots can be done the 'factoring in pairs' way.

 

Yours is 

$$\\2(x^2+4x-6)=0\\\\
x^2+4x-6=0\\\\$$

 

Now you have to look for 2 numbers that multiply to 1*-6=-6

Since they multiply to a negative, one is pos and the other is neg

They have to add to +4

So the 'bigger' (absolute value) one is positive

There are no 2 rational numbers that meet this requirement so you cannot do it this way!

 

There are a number of methods that you can use.

Alan has shown you one of them.

I would just solve it using the quadratic formula :))

Melody  Aug 17, 2015
 #4
avatar+91051 
+5

Now to answer you real question.

Where did I go wrong!

 

 

 

I expect you know that   

$$\\3a+4a=(3+4)a\\\\
and\\\
xa+6a = (x+6)a\\\\
$say a was not $a$ but just some expression.$\\\\
3(x+2)+4(x+2\\=3 \; lots\; of\; (x+2)+4 \; lots\; of\; (x+2)\\= (3+4)\; lots\; of\; (x+2) \\= 7(x+2)\\\\
x(x+2)+6(x+2)\\=x \; lots\; of\; (x+2)+6 \; lots\; of\; (x+2)\\= (x+6)\; lots\; of\; (x+2) \\= (x+6)(x+2)\\\\$$

 

Now, this is what you wrote:

$$\\x(x-2)+6(x-1)\\\\(x+6)(2x-3)\\$$

You cannot do this because you have x lots of (x-2)  and 6 lots of (x-1)  

The brackets are not the same - they are unlike terms - you cannot add them like you have done :/

Melody  Aug 17, 2015

4 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details